HUBUNGAN STATUS GIZI DAN GAYA HIDUP DENGAN KEJADIAN PRADIABETES PADA REMAJA DI DKI JAKARTA - Nadila Fitri (2023)
Prediabetes is a condition in which an individual has blood glucose levels higher than normal but not high enough to be categorized as diabetes. DKI Jakarta province has a relatively high prevalence of prediabetes cases, and there has been an increase in cases of diabetes mellitus in 2018. Information regarding the risk factors for prediabetes among individuals aged ≥15 years in DKI Jakarta is essential to ensure that control efforts yield optimal results. This study aims to analyze the relationship between nutritional status, lifestyle, and the incidence of prediabetes among adolescents in DKI Jakarta. The research design used was cross-sectional, with a sample size of 108 respondents selected using a stratified random sampling technique. Based on the Chi-Square test results, it was found that there is no relationship between nutritional status (BMI for age) and the occurrence of prediabetes (p = 0.088). There is no association between waist circumference and the occurrence of prediabetes (p = 0.452), no relationship between physical activity and the occurrence of prediabetes (p = 1.000), and no association between dietary patterns and the occurrence of prediabetes (p = 0.665). Further research is recommended to use fasting blood glucose to establish the diagnosis, analyze energy intake, and use a larger sample size to provide a clearer relationship.